Who Owns the Past? Archaeological Heritage between Idealisation and Destruction - Gori, Maja; Pintucci, Alessandro; Revello Lami, Martina (Ex Novo: Journal of Archaeology, 2017)
On the 23rd of August 2015 Daesh blew up the 2,000-year-old Baal-Shamin temple in the world-famous Greco-Roman site of Palmyra. This event triggered a profound emotional reaction in society at large, and the ruins soon became an iconic symbol of world heritage in danger. The appalling images of the ruins of Baal Shamin reinforced the perception, especially among western observers, that protecting cultural and natural heritage is yet another duty in the fight against terrorism. A similar international outcry occurred in 2001, when the Buddhas of Bamiyan fell to Taliban dynamite in Afghanistan, and when Iraqi museums and sites were ransacked and looted providing two of the most recent and vivid examples of destroyed heritage in the so-called War on Terror which was launched by the U.S. government after 9/11. Following the destruction at Baal-Shamin, UNESCO declared that the deliberate destruction of Syria’s cultural heritage was a war crime, and put into motion several projects and actions aimed at preserving endangered Syrian archaeological heritage. At the same time, alongside income gained from the sale of drug and weapons, the trafficking of antiquities from Syria and Iraq worldwide provided a major source of revenue for Daesh.